The Effect of Pelvic Rocking on Back Pain Intensity in Third Trimester Pregnant Women - Huda Rohmawati; Weni Tri Purnani; Dessy Lutfiasari; Agung Nugroho Widhi (Journal of Global Research in Public Health, 2023)
Pregnancy is a physiological process. The most common complaint at the end of the trimester is lower back pain. These complaints will increase in the final trimester of pregnancy, resulting in disrupted daily routine. Various reports state that in pregnant women it is recorded that about 50% of women experience back pain and about 10% of women with chronic back pain begin during pregnancy. Lower back pain is experienced a lot when entering the 6th month of pregnancy. The purpose of this study was to prove that hip rocking has an effect on the intensity of back pain in the third trimester of pregnant women. The research design was a quasi-experiment with one group pretest-postest design. The sample in this study were 21 respondents of third trimester pregnant women. Observation sheet research instrument. The results were analyzed using the Wilcoxon signed ranking statistical test. The results showed that pelvic sway was able to significantly  reduce the intensity of back pain in third trimester pregnant women. Therefore, third trimester pregnant women can be given hip rocking therapy as an alternative to non-pharmacological interventions to reduce back pain during pregnancy.